PELINDUNGAN DATA PRIBADI DI INDONESIA: IUS CONSTITUTUM DAN IUS CONSTITUENDUM - Glenn Wijaya (Law Review, 2020)
AbstractCases of leakage and misuse of personal data continue to increase in Indonesia along with the increasing activity of the digital economy, especially in the era of the COVID-19 pandemic. However, the existing laws and regulations, or what is called as the ius constitutum relating to the protection of personal data are still sectoral in nature so that they are not centralized and there are no regulations at the level of law, so that criminal sanctions are not maximally applied to criminals in this sector. Now, the Indonesian House of Representatives (DPR) is drafting a Personal Data Protection Bill (“PDP Bill”), which in general follows the standards set out in the GDPR, which in the near future is expected to become an ius constitutum that can solve problems related to the protection of personal data in Indonesia. In this article, the author will discuss what are the shortcomings of the existing ius constitutum and also discuss new things and criticisms of the provisions in the ius constituendum, namely the PDP Bill. The research method used by the author is normative legal research by examining, primarily, the existing laws and regulations in Indonesia relating to the protection of personal data along with the PDP Bill. The author then also provides several recommendations to the Government, Electronic System Administrators, and also the general public regarding the development of the PDP Bill and the status quo of personal data protection in Indonesia. Keywords: Personal Data Protection, Ius Constitutum, Ius Constituendum AbstrakKasus kebocoran dan penyalahgunaan data pribadi terus meningkat di Indonesia seiring dengan meningkatnya aktivitas ekonomi digital, terlebih di era pandemi COVID-19. Namun, peraturan perundang-undangan yang sudah ada, atau disebut ius constitutum terkait pelindungan data pribadi masih bersifat sektoral sehingga belum terpusat dan tidak ada pengaturan di setingkat undang-undang, sehingga sanksi pidana pun masih belum maksimal diterapkan kepada para pelaku kejahatan di sektor ini. Kini, DPR sedang menyusun RUU Perlindungan Data Pribadi (“RUU PDP”), yang secara garis besar mengikuti standar yang ada dalam GDPR, yang dalam waktu dekat diharapkan akan menjadi ius constitutum yang dapat mengatasi permasalahan terkait pelindungan data pribadi di Indonesia. Dalam artikel ini, Penulis akan membahas apa saja yang menjadi kekurangan dari ius constitutum yang ada dan juga mengupas apa saja hal-hal baru beserta kritik terhadap pengaturan dalam ius constituendum, yaitu RUU PDP. Metode penelitian yang dipakai Penulis adalah penelitian hukum secara normatif dengan mengkaji, terutama, peraturan perundang-undangan yang sudah berlaku di Indonesia terkait dengan pelindungan data pribadi beserta draf RUU PDP. Penulis lalu juga memberikan beberapa rekomendasi kepada Pemerintah, Penyelenggara Sistem Elektronik, dan juga masyarakat umum terkait perkembangan RUU PDP dan status quo pelindungan data pribadi di Indonesia.Kata Kunci: Pelindungan Data Pribadi, Ius Constitutum, Ius Constituendum